Zur Wertigkeit der kombinierten computerunterstützten Perfusionsszintigraphie und Renographie bei Oligurie/Anurie von nierentransplantierten Patienten - Miserez, A. (Nuklearmedizin - NuclearMedicine, 1989)
Combined computer-aided perfusion scintigraphy and renography (computer renography) is used for the differential diagnosis of the etiology of transplant malfunctions in kidney-transplant patients. This article describes semiquantitative computer renography evaluation methods which have been used in 99 examinations of 58 oligo/anuric graft recipients. The accuracy of these methods was confirmed by patho-anatomical and roentgenological diagnosis. From the constellation of qualitative and semiquantitative scintigraphic perfusion, function and excretion parameters it was possible, by means of a flow chart, to draw conclusions regarding the location of the malfunctions (prerenal, renal or postrenal). Using the new methods, all patients could be correctly classified. With respect to more detailed differential diagnosis of renal malfunctions the accuracy was 82%. The comparison between perfusion measurements based on a perfusion index defined with the help of a planimeter on the one hand and an angiography graduation on the other hand, resulted in a correlation coefficient of 0.90 (p < 0.001). As a non-invasive examination which can also be carried out in emergency cases, combined computer-aided perfusion scintigraphy and renography should become part of standard diagnostic procedures for oligo/anuric graft recipients.